A couple-stress model to predict the wrinkling stress of sandwich panels with foam cores. (15th July 2021) - Su, Wenzheng; Liu, Shutian
Abstract: Wrinkling is a common failure mode of sandwich panels under in-plane compression. The classic methods often underestimate the wrinkling stress, especially for sandwich panels with low-relative-density foam cores. Hence, an accurate method for predicting wrinkling stress is desirable. This study proposes a new method to compute the wrinkling stress of sandwich panels. The foam core was taken as a couple-stress continuum with characteristic length, and the bending deformation of core materials was contained in the strain energy computation. The results showed that the predicted wrinkling stress agreed dramatically well with the experimental data. The computed wrinkling stress showed a significant size dependence on the cell size of the foam core. The bending deformation of the core material was significant for large characteristic length. Hence, our method expanded the classic work on predicting the wrinkling stress of sandwich panels, and we suggest that it should be used in the wrinkling analysis of sandwich panels with cellular solids.